Experimental investigations on recycled aggregate concrete-filled stainless steel tube stub columns - Ngin, Dennis Cheong Jun (Nanyang Technological University, 2023)
This report experimentally investigates the compressive behavior of RACFSST (recycled aggregate concrete filled stainless steel tubular) stub columns. Twelve stub columns were equally fabricated from the square and circular hollow stainless-steel outer tubes infilled with concrete of three levels of recycled coarse aggregate replacement rates (by weights), namely 0%, 35%, and 70%. The performed testing program comprised cylinder tests, tensile coupon tests, and compression tests. The European, Australian, and American standards were examined against the experimental results of RACFSST stub column specimens. The estimation showed that square RACFSST stub columns should be designed in accordance with American code with the mean value of Nu/Nu, AISC being 1.05, while the dimensions of circular RACFSST stub columns should be determined according to European and Australian Standards, with the with the mean value of Nu/Nu, EC4 and Nu/Nu, AS being 1.03 and 1.04 respectively.